ARTISTIC INTEGRATIVE TECHNOLOGIES IN POLYART EDUCATION - Baranovska І. Г. (Journal of Information Technologies in Education (ITE), 2018)
Тhe article deals with the modernization of higher pedagogical education, the introduction of innovative approaches, the development of artistic integrative technologies, changes in the classical forms of teaching future teachers. It has been established that poly-artistic education is a poly-artistic upbringing and development, a poly-artistic approach to the implementation of the educational process. Polyart education is based on the universal possibilities of art, its multifunctional nature. The concept of "integration of the arts" in poly-art education is analyzed. The characteristic levels and types of integration. The features of integration as an innovative educational technology are considered. The explication of integrative art technologies developed on the basis of immersion in the artistic heritage, live communication with works of art, dialogue with the museum subject is presented. The quest is considered as an integrative game art-pedagogical technology, interesting for children and adults. It has been proven that the development of quest art integrative technologies makes it possible to successfully use the possibilities and advantages of computer audio-visual technologies in educational work with students and young people; motivates to obtain new artistic knowledge, improve performing skills, creative search, self-improvement and self-realization. A number of special programs for creating web quests, animation, video presentations, phonogram writing, working with a microphone have been described. Further research requires studying the experience of introducing integrative art technologies in the educational process of secondary and higher schools in Europe, Asia, America, improving the mechanisms of poly-artistic integrative impact on different age categories of students and young people, developing integrative art technologies for poly-artistic education of children of preschool and primary school age.